Biocontrol potential of rice endophytic fungi against phytopathogens in East Kalimantan, Indonesia - SOPIALENA SOPIALENA; KADIS MUJIONO; SYAKHRIL SYAKHRIL; NURHASANAH NURHASANAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sopialena, Mujiono K, Syakhril, Nurhasanah. 2025. Biocontrol potential of rice endophytic fungi against phytopathogens in East Kalimantan, Indonesia. Biodiversitas 26: 5737-5754. Endophytic fungi are increasingly recognized for their potential as eco-friendly biocontrol agents in sustainable agriculture. This study aimed to isolate, identify, and evaluate the antagonistic potential of rice endophytic fungi across diverse agroecosystems in Penajam Paser Utara, Samarinda, and Kutai Kartanegara, East Kalimantan, Indonesia. Endophytic fungi were isolated from healthy rice plants and screened for antagonism against five pathogens using dual-culture assays. A total of six fungal genera were identified, including Aspergillus niger, Penicillium sp., Rhizopus sp., Trichoderma sp., Gliocladium sp., and Paecilomyces sp., with A. niger, Penicillium sp., and Rhizopus sp. being the most frequently isolated. Morphological characterization revealed distinct colony and microscopic traits supporting genus-level identification. Results of antagonistic assays against the five major rice pathogens Magnaporthe oryzae, Fusarium sp., Cercospora sp., Rhizoctonia solani, and Curvularia sp. demonstrated that endophytic fungi employed mechanisms, such as competition, parasitism, and antibiosis to suppress pathogen growth. The inhibitory activity of endophytic fungal isolates varied significantly, with inhibition rates ranging from 36.25% to 85%. The highest levels of inhibition were recorded against Fusarium sp. (81.11%), Cercospora sp. (85.00%), Rhizoctonia solani (85.00%), and Curvularia sp. (76.44%), while moderate inhibition was observed against M. oryzae (54.18%). Among the isolates, Rhizopus sp. and Gliocladium sp. consistently demonstrated the strongest antagonistic activity across multiple pathogens. The variability in inhibition rates highlights the importance of strain specificity, pathogen susceptibility, and host-endophyte compatibility in determining biocontrol efficacy. These fungi offer eco-friendly alternatives to chemical pesticides.